2013
DOI: 10.2337/dc12-2141
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Diabetic Retinopathy and Cognitive Impairment

Abstract: OBJECTIVERecent studies have shown an increased risk for cognitive impairment and dementia in patients with diabetes. An association between diabetic retinopathy (DR) and retinal microvasculature disease and cognitive impairment has been reported as potential evidence for a microvascular component to the cognitive impairment. It was hypothesized that severity of DR would be associated with cognitive impairment in individuals with type 2 diabetes.RESEARCH DESIGN AND METHODSThree hundred eighty patients with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 32 publications
(39 reference statements)
4
51
2
3
Order By: Relevance
“…A longitudinal study (n=180), reported that the presence of diabetic retinopathy assessed prior to coronary surgery was associated with an increased risk of cognitive decline after 6 months following surgery [9]. Other studies reported no association between diabetic retinopathy and cognition [11,12] nor with cognitive decline after 4 years [11]. Possible explanations for the negative findings of some of these studies include limited sample sizes (consequently including few retinopathy cases e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A longitudinal study (n=180), reported that the presence of diabetic retinopathy assessed prior to coronary surgery was associated with an increased risk of cognitive decline after 6 months following surgery [9]. Other studies reported no association between diabetic retinopathy and cognition [11,12] nor with cognitive decline after 4 years [11]. Possible explanations for the negative findings of some of these studies include limited sample sizes (consequently including few retinopathy cases e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[11], different levels of severity of diabetic retinopathy (i.e. also including non-proliferative diabetic retinopathy a less severe form of diabetic retinal disease) [11] and exclusion of patients with dementia and stroke which could lead to an underestimate of the level of cognitive impairment [12]. Of note the relation between diabetic retinopathy and cognition has also been studied in patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Associations between DR and cognitive impairment have been reported for an older and population-based sample of a different ethnicity in which only a third had diabetes. 20 Associations between DR and cognitive impairment have been reported for an older and population-based sample of a different ethnicity in which only a third had diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies that showed association between diabetic retinopathy and cognitive impairment, with a near threefold increased risk of cognitive impairment in patients with diabetic retinopathy compared to those without. (20) In our study population, out of the 140 patients, 30% had MMSE scores <24, thus demented at baseline. The highest score was 29 and the lowest was 13.…”
Section: Discussionmentioning
confidence: 99%